(untitled) (ARQUISUR Revista, 2024)
When it comes to expressing the flexibility of uses of the domestic space, the floor plan is the most appropriate graphic piece. This paper reflects on the relationships that exist between the design ideas that support the proposals and the graphic resources used by designers to communicate them. With this objective, the flexible modality called versatile floor plan is analyzed. It is considered as an initial flexibility since it is developed before users’ occupation. To carry out this reflection, the ideas of different authors who have theorized about flexible housing are opened to discussion. Second, as an illustration of the studied theoretical concepts, the analysis of a series of projects and accomplished works is performed. These proposals are presented by means of plan drawings published by designers themselves to explain their ideas. From the study of the floor plans, a series of conclusions are drawn about the use of the aforesaid graphics as discursive tools at the service of the project.